Identification of the source of elevated hepatocyte growth factor levels in multiple myeloma patients - Rampa, Christoph (BioMed Central, 2014)
BACKGROUND: Hepatocyte growth factor (HGF) is a pleiotropic cytokine which can lead to cancer cell proliferation, migration and metastasis. In multiple myeloma (MM) patients it is an abundant component of the bone marrow. HGF levels are elevated in 50% of patients and associated with poor prognosis. Here we aim to investigate its source in myeloma. METHODS: HGF mRNA levels in bone marrow core biopsies from healthy individuals and myeloma patients were quantified by real-time PCR. HGF gene expression profiling in CD138(+) cells isolated from bone marrow aspirates of healthy individuals and MM patients was performed by microarray analysis. HGF protein concentrations present in peripheral blood of MM patients were measured by enzyme-linked immunosorbent assay (ELISA). Cytogenetic status of CD138(+) cells was determined by fluorescence in situ hybridization (FISH) and DNA sequencing of the HGF gene promoter. HGF secretion in co-cultures of human myeloma cell lines and bone marrow stromal cells was measured by ELISA. RESULTS: HGF gene expression profiling in both bone marrow core biopsies and CD138(+) cells showed elevated HGF mRNA levels in myeloma patients. HGF mRNA levels in biopsies and in myeloma cells correlated. Quantification of HGF protein levels in serum also correlated with HGF mRNA levels in CD138(+) cells from corresponding patients. Cytogenetic analysis showed myeloma cell clones with HGF copy numbers between 1 and 3 copies. There was no correlation between HGF copy number and HGF mRNA levels. Co-cultivation of the human myeloma cell lines ANBL-6 and JJN3 with bone marrow stromal cells or the HS-5 cell line resulted in a significant increase in secreted HGF. CONCLUSIONS: We here show that in myeloma patients HGF is primarily produced by malignant plasma cells, and that HGF production by these cells might be supported by the bone marrow microenvironment. Considering the fact that elevated HGF serum and plasma levels predict poor prognosis, these findings are of particular importance for patients harbouring a myeloma clone which produces large amounts of HGF.